Do ultra-poor graduation programmes build resilience against droughts? Evidence from rural Ethiopia - Hirvonen, Kalle; Gilligan, Daniel O.; Leight, Jessica; Tambet, Heleene; Villa, Victor (VoxDev, 2024)
A growing body of evidence now suggests that global warming increases the risk of extreme weather events such as droughts, floods, and tropical cyclones (Seneviratne et al. 2021), and these shocks often force poor households to consume less or sell valuable assets, worsening their food security and increasing their vulnerability to chronic poverty. These effects can be particularly salient for women, who often have less resources than male family members even within poor households (Fruttero et al. 2023, van Daalen et al. 2020), and who may face increased vulnerability to violence (Abiona and Koppensteiner 2018, Díaz and Saldarriaga 2023, Epstein et al. 2020). The high and growing incidence of climate-related shocks has only increased the importance of identifying interventions that can strengthen households’ resilience against the adverse consequences of these shocks.